Concentration of Institutions and Urban Bias in India - Varghese, N.V.; Panigrahi, Jinusha (International Higher Education, 2019)
Higher education development in India shows signs of concentration and urban bias. As in many countries, the permeation of market processes and proliferation of private higher education institutions seem to have contributed to increased regional inequalities. Relying on the concentration ratio, a measure developed by a CPRHE/NIEPA research study, this article discusses the nature and extent of regional inequalities in the current provision of higher education and identifies locations to be prioritized for establishing new institutions to level off regional inequalities in the future.